2018
DOI: 10.1002/csr.1488
|View full text |Cite
|
Sign up to set email alerts
|

The social reputation of European companies: Does anti‐corruption disclosure affect stakeholders' perceptions?

Abstract: Corruption is a very important topic in society but also for businesses. However, there are few empirical studies that analyze corruption from the point of view of disclosure by companies and none that analyze its effect in corporate reputation. The aim of this paper is to use stakeholder theory to analyze the potential power of reporting in influencing stakeholders' perceptions and communication tools, such as sustainability reports, to bolster corporate reputation in relation to the social issue of corruptio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
29
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 74 publications
(106 reference statements)
2
29
1
Order By: Relevance
“…Existing research indicates that the intensive industry competition encourages firms to disclose CSR information [38]. This finding is also consistent with cross-country studies that indicated that firm level corruption was negative associated with firm social reputation [35] and CSR performance [36], and that the level of corruption in a country was negatively related to firms' CSR information disclosure [33]. Our explanation of this finding is that when firms are less likely to seek "rents" from corruption under the pressure of intensive anti-corruption actions, they are more likely to disclose CSR information.…”
Section: Impact Of Regional Anti-corruption Intensity On Firms' Disclsupporting
confidence: 85%
See 1 more Smart Citation
“…Existing research indicates that the intensive industry competition encourages firms to disclose CSR information [38]. This finding is also consistent with cross-country studies that indicated that firm level corruption was negative associated with firm social reputation [35] and CSR performance [36], and that the level of corruption in a country was negatively related to firms' CSR information disclosure [33]. Our explanation of this finding is that when firms are less likely to seek "rents" from corruption under the pressure of intensive anti-corruption actions, they are more likely to disclose CSR information.…”
Section: Impact Of Regional Anti-corruption Intensity On Firms' Disclsupporting
confidence: 85%
“…The central government of China is aware of the harm caused by corruption and has vigorously implemented a high-pressure anti-corruption policy. There is evidence of the relationships between firm level corruption and firm social reputation [35] and CSR performance [36] as well as a relationship between country level corruption and a firm's CSR information disclosure [33]. Will anti-corruption actions in transition economies impact on firms' disclosure of CSR?…”
Section: Literature Review and Hypothesesmentioning
confidence: 99%
“…Breen et al () find that both women in top management positions and female owners are associated with less corruption. Recently, Álvarez Etxeberria and Aldaz Odriozola () show that corporate anticorruption disclosure positively influences firms' reputations.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In the corporate context, several publications have analyzed the relationship between the company's reputation and the contents of social and environmental reports (e.g., Koprowski et al, 2019;Odriozola & Baráibar-Diez, 2017). Other types of reports can also be included when addressing, for example, the image of a "corrupt" company and its relationship with interest groups (e.g., Barros, Rodrigues, & Panhoca, 2019;Etxeberria & Odriozola, 2017).…”
Section: Review Of the Literaturementioning
confidence: 99%
“…The underlying assumption is that companies adopt communication strategies in their financial reports to assure their survival (Dowling & Pfeffer 1975;Odriozola & Baráibar-Diez, 2017). Such strategies are particularly aimed to: 1) influence the society's perceptions (Barros, Rodrigues, & Panhoca, 2019;Deegan, 2002;Guthrie & Parker, 1990), 2) lead interested parties to support the company with positive responses (Barros, Rodrigues, & Panhoca, 2019), and 3) consequently, gain or preserve social legitimacy (Etxeberria & Odriozola, 2017;Neu, Warsame, & Pedwell, 1998).…”
Section: Review Of the Literaturementioning
confidence: 99%